Conjugate natural convection inside a vertical enclosure with solid obstacles of unique volume and multiple morphologies. (April 2016) - Hu, Jiang-Tao; Ren, Xiu-Hong; Liu, Di; Zhao, Fu-Yun; Wang, Han-Qing
Highlights: Conjugate natural convection is studied with two morphologies of obstacles. The amount of solid constituent of both two configurations is kept constant. Minimum number of obstacles required for gap flow decay was analyzed. Nusselt number increases with Ra and Kr and decreases with γ and N . NuB is higher than NuA for low γ, and it reverses for high volume ratio. Abstract: Effect of the solid obstacles on the natural laminar convection in a vertical enclosure is numerically and analytically investigated in the present work, aiming to identify suitable arrangements for heat transfer enhancement in the electronic cooling units. Two categories of morphology were taken into considerations, being attached to the horizontal walls and being placed centrally in the space. Thermal Rayleigh number, number of obstacles, and solid thermal conductivity have been varied to observe inherent flow structures and thermal transport mechanism, regarding of different levels of solid-to-fluid volume ratios. Flow field, thermal field and heat transfer rates are respectively visualized through streamlines, isotherms and heatlines. Depending on a large set of numerical data and critical boundary layer analysis, correlations have been developed for these two fundamental configurations. Results demonstrate that average Nusselt number is an increasing function of Ra and Kr and a decreasing function of γ and NA (and NB ). Furthermore, average Nusselt number of enclosure B is greater than that of enclosure A when volume ratio is lower, while this phenomenon is contrary as the volume ratio and relative obstacles number increases. These two configurations of obstacles number are important to optimize the cooling efficient of electronic components.